2021
DOI: 10.3390/agronomy11091877
|View full text |Cite
|
Sign up to set email alerts
|

Tuning Potassium and Magnesium Fertilization of Potato in the South of West Siberia

Abstract: Imbalance of nutrients limits crop yields. Although K fertilization receives sufficient attention in research and practice, Mg supply is rather neglected. The effect of Mg fertilization (0, 5 and 10 g Mg/m2), combined with two K fertilization rates (10 and 15 g K/m2), on potato production and soil exchangeable K and Mg was studied in a three-season microplot field experiment in the Novosibirsk region, Russia. Tuber yield did not respond to the increased K fertilization, but increased at 5 and decreased at 10 g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…On the contrary, in the control variant of the experiment on Luvic Greyzemic Phaeozem soil, the content of easily exchangeable magnesium significantly decreased in comparison with virgin soil. The level of humus in this soil during its agricultural use has significantly decreased (Table 2) and the cultivation of row crops contributed to a certain activation of the leaching processes; it is known that magnesium ions have an increased migratory ability (Senbayram et al, 2015;Chernousenko et al, 2023) In addition, the removal of the element with the alienated main and secondary plant products could also have a certain effect (Yakimenko and Naumova, 2021).…”
Section: Resultsmentioning
confidence: 99%
“…On the contrary, in the control variant of the experiment on Luvic Greyzemic Phaeozem soil, the content of easily exchangeable magnesium significantly decreased in comparison with virgin soil. The level of humus in this soil during its agricultural use has significantly decreased (Table 2) and the cultivation of row crops contributed to a certain activation of the leaching processes; it is known that magnesium ions have an increased migratory ability (Senbayram et al, 2015;Chernousenko et al, 2023) In addition, the removal of the element with the alienated main and secondary plant products could also have a certain effect (Yakimenko and Naumova, 2021).…”
Section: Resultsmentioning
confidence: 99%
“…However, recent research has shown that cassava yields increase if fertilizer is applied [4,5]. Among the factors limiting cassava yields, nutrient imbalances and/or deficiencies have received little attention, yet, are likely to contribute to a large portion of the current yield gap [6,7].…”
Section: Introductionmentioning
confidence: 99%